Double Roles of Married Working Women in Indonesia: For Better or for Worse? - Purwanto, Deniey A. (The Indonesian Forestry Certification Cooperation, 2021)
SDGs 2030 have at least two goals that strongly converged to gender equality of pay, gender equality (Goal 5), and decent work and economic growth (Goal 8). Marital status argued to have significant contribution in gender inequality of pay and the root of female wage penalty. The argument associated with traditional family division of labour, where men responsible for family breadwinner and women for family caregiver. We examine this argument in Indonesia experiences with additional feature of multiple breadwinner models in the family. Utilizing Indonesian National Labour Force Survey of 2015 of more than 150.000 workers, our twofold regression compatible Oaxaca-Blinder decomposition analysis confirmed the existence of statistically significant gender wage gap even when controlling for the human capital investment, family division of labour, institutional instrument and discrimination. Our findings suggest that married women tend to take a double roles than married men, being family breadwinner as well as family caregiver. In that double roles model, wage rate are highest among working women and marriage wage penalty died out. Unfortunately gender wage gap and wage discrimination persisted. While the role of minimum wage as current nominal institutional labour market instrument still trivial, other factors must also be addressed toward gender equality of pay and more efficient labour market.